2002
DOI: 10.1063/1.1483383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amorphizing species’ ion mass on the end-of-range damage formation in silicon

Abstract: The effects of preamorphizing ion mass on the end-of-range (EOR) damage and subsequent enhanced diffusivity have been investigated. Amorphizing silicon with implants of 22 keV 28Si+, 32 keV 73Ge+, 40 keV 119Sn+, and 45 keV 207Pb+ provided the mass comparisons. Cross-sectional transmission electron microscopy analysis showed that the amorphous layer depths were approximately 400 Å. After postimplantation annealing at 750 °C for 30 min, plan-view transmission electron microscopy (PTEM) revealed that increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…After recrystallization, a very low concentration of residual defects is found at the end of range of lithium ion. In contrast to what was observed by Clark et al, 33 who showed that increase of the ion mass decreases the population of interstitial trapped in the EOR, this study shows that for low temperature implantation, low ion mass induces less defects.…”
Section: Discussioncontrasting
confidence: 99%
“…After recrystallization, a very low concentration of residual defects is found at the end of range of lithium ion. In contrast to what was observed by Clark et al, 33 who showed that increase of the ion mass decreases the population of interstitial trapped in the EOR, this study shows that for low temperature implantation, low ion mass induces less defects.…”
Section: Discussioncontrasting
confidence: 99%
“…This result suggests that the dissolution of the EOR damage during the thermal annealing enhances the deactivation. The fact that the deactivation in the Sb-doped samples is independent of laser fluence, either indicates that the deactivation of Sb is not affected by the EOR damage, or that the EOR damage takes on a different morphology in the Sb preamorphized samples due to its greater ion mass than silicon [17]. These results demonstrate the importance of removing all implant damage from the samples in order to maintain full electrical activation of dopants.…”
Section: Resultsmentioning
confidence: 81%
“…These implant conditions have to be properly modeled since ions such as Ge or As are frequently used in the manufacturing of Si devices as preamorphizing steps [49,50], and molecular implants with octadecaborane are considered as an alternative to monatomic B implants because they are self-amorphizing and minimize residual damage [51].…”
Section: Towards a Comprehensive Description Of Ion-implanted Damagementioning
confidence: 99%